Peningkatan Pengetahuan Terkait Hipertensi Guna Perbaikan Tekanan Darah pada Pemuda di Dusun Japanan, Margodadi, Seyegan, Sleman, Yogyakarta - Erica Kusuma Rahayu Sudarsono; Julius Fajar Aji Sasmita; Albertus Bayu Handyasto; Natalia Kuswantiningsih; Stefanus Sofian Arissaputra (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
Prevalence of hypertension in Indonesia  has reached 25.8%; Yogyakarta is the third largest prevalence in Indonesia, and hypertension in Seyegan sub-district is ranked first most diagnosed. Hypertension can lead to an increased risk of cardiovascular diseases such as heart attacks and strokes. Knowledge related to hypertension of residents, especially youth is still quite low. Youth is provided with education and training on how to measure blood pressure and basic knowledge related to hypertension. The education was done by discussion using Focus Group Discussion (FGD) method, then youth made program to overcome hypertension problem. Conducted blood pressure screening and interviews about the lifestyle of residents to determine the cause of hypertension. Blood pressure screening and interviews were analyzed by chi square or fisher, increased youth knowledge from pre-test and post-test analyzed with kolmogorov-smirnov and analyzed by paired T test with 95% confidence level. There was no significant effect between BMI, education and exercise on blood pressure, but there was a significant influence between smoking and consumption of foods high in salt and fat to blood pressure. The results of pre-test and post-test showed an increase in youth knowledge from the beginning only 5.27 to 7.37 with p-value 0.000 (p <0.05). Provision of education to youth increases the level of knowledge related to hypertension.